Effect of curcuma longa extract (curcumin c3 complex) on αlpha glucosidase inhibition and dpp- iv inhibition Activity – an in-vitro study - S.D.INBARAJ,; M.MUNIAPPAN, (International Journal of Pharma and Bio Sciences, 2018)
Curcumina longa has been under various scientific research for its therapeutic potential. The effect of Curcuma longa extract (Curcumin C3 Complex) on the inhibition of α-glucosidase and Dipeptidyl Peptidase-4 DPP IV enzyme activity by in-vitro method was investigated for its antihyperglycemic and antidiabetic potential. Ethyl acetate extract of Curcuma longa rhizomes ( Curcumin C3 Complex) was prepared and supplied by Sami labs, Bangalore on request. For α-glucosidase inhibitory assay curcumina longa extract concentrations of (0,29,38,52,63,72 µg/ml) and for DPP-IV inhibition assay ( 0,5,10,20,40,80,160,320 µgm/ml) concentrations were used.. The absorbance was measured at 405 nm using multi plate reader and the percentage of α-glucosidase inhibitory activity was recorded. For DPP IV inhibition the initial measurement (T initial)and final (T final) fluorescence intensity (FLU) initial, lex = 360/lem = 460 nm) were recorded. Percentage of DPP IV enzyme inhibitory activity was determined. The maximum percentage inhibitory activity of alpha-glucosidase by Curcumin and Acarbose (STD) at 100 μg/ml was 72 % and 94% respectively. The maximum % of DPP IV inhibition of Curcumin and Vildagliptin (STD) at 320 μg/ml were 76.47% and 80.15% respectively. The results of the in vitro studies show Curcuma longa (Curcumin C3 Complex) has significant alpha glucosidase and DPP IV inhibition. Further in vivo and clinical studies are necessary to establish the antihyperglycemic and antidiabetic potential of Curcuma longa for the treatment of type 2 diabetes mellitus.